A Recommender for Choosing Data Systems based on Application Profiling and Benchmarking - Soares, Elton Figueiredo de Souza; Souza, Renan; Thiago, Raphael Melo; Machado, Marcelo de Oliveira Costa; Azevedo, Leonardo Guerreiro (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2021: Anais do XXXVI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2021.17883, 2021)
In our data-driven society, there are hundreds of possible data systems in the market with a wide range of configuration parameters, making it very hard for enterprises and users to choose the most suitable data systems. There is a lack of representative empirical evidence to help users make an informed decision. Using benchmark results is a widely adopted practice, but like there are several data systems, there are various benchmarks. This ongoing work presents an architecture and methods of a system that supports the recommendation of the most suitable data system for an application. We also illustrates how the recommendation would work in a fictitious scenario.